Islamic State enters Al-Qaeda's old hotbed: Afghanistan and Pakistan - Mona Kanwal Sheikh (Danish Institute for International Studies (DIIS), 2016)
Ten years ago, the borderlands between Pakistan and Afghanistan were the command post for leaders of Al-Qaeda (AQ). But what has happened with AQ since then? And what sort of collaboration or conflict is there between the dominant Taleban-related movement in the region, AQ, and the new kid in town; Islamic State (IS)? Below I look at the emergence of IS in Afghanistan and Pakistan and at the dynamics that have impacted the relationship between the "old" movements in the region (Taleban and AQ) on the one hand, and IS on the other. IS is still a fledgling movement in the "afpak" region, and therefore there is still no clear picture of its influence and resonance in Afghanistan and Pakistan. Because the situation is still unfolding, this article is based on very limited source material about the movement.
Keywords: 330